An Introduction to analytic geometry and calculus - Burdette, Albert Clark (New York : Academic Press, 1973)
This edition follows the same plan and is intended to serve the same purposes as the original one. An Introduction to Analytic Geometry and Calculus covers the basic concepts of analytic geometry and the elementary operations of calculus. This book is composed of 14 chapters and begins with an overview of the fundamental relations of the coordinate system. The next chapters deal with the fundamentals of straight line, nonlinear equations and graphs, functions and limits, and derivatives. These topics are followed by a discussion of some applications of previously covered mathematical subjects. This text also considers the fundamentals of the integrals, trigonometric functions.
1. The coordinate system - fundamental relations -- 2. The straight line -- 3. Nonlinear equations and graphs -- 4. Functions and limits -- 5. The derivative -- 6. Some applications -- 7. The integral -- 8. The trigonometric functions -- 9. The exponential and logarithm functions -- 10. Methods of integration.
Includes index.
Keywords: CALCULUS